Population assessment of whitefly (Bemisia tabaci (Genn.)) for ten tomato genotypes - Malik H. Karem; Ali Faraj Jubair; Saad Manea Enad Aljabry; Mahmood T. Al-Jayashi (Zien Journals, 2022)
The field tests were conducted during the The field tests were carried out during the 2021-2022 growing season. The experiment was designed in a randomized complete block design (RCBD). Ten tomato genotypes were tested to determine their tolerance or sensitivity to whitefly insect infection and the extent of the insect's nutritional preference for any cultivated genetic structure, as the whitefly insect destroys tomato production in Iraq by absorbing plant juices and transmitting viruses, including the Tomato yellow leaf curl virus (TYLCV), which is a major problem for tomato production in Iraq. In terms of plant height, the Camry F1 genotype had the lowest decrease in chlorophyll percentage, the Faten F1 genotype had the highest, while the Romeo F1 genotype had the lowest productivity among the tested genotypes. The genotype for the number of adult whiteflies was Star F1. The least preferred and most appealing to the insects' adults.
Keywords: Bemisia tabaci; Genotypes; Tomato; Tolerance